Brief Report: Cystatin C-Based Estimation of Glomerular Filtration Rate and Association With Atherosclerosis Imaging Markers in People Living With HIV. (1st December 2020) - McClean, Mitchell; Buzkova, Petra; Budoff, Matthew; Estrella, Michelle; Freiberg, Matthew; Hodis, Howard N.; Palella, Frank; Shikuma, Cecilia; Post, Wendy S.; Gupta, Samir
Abstract : Introduction: Reduced estimated glomerular filtration rate (eGFR) is associated with increased risk of cardiovascular disease among people living with HIV (PLWH). It is unclear whether eGFR equations incorporating cystatin C (CysC) measurements are more predictive of preclinical cardiovascular disease than those using only creatinine (Cr). Objectives: The study aimed to determine which of the 3 Chronic Kidney Disease Epidemiology (CKD-EPI) eGFR equations is most associated with carotid intima media thickness (CIMT) and coronary artery calcium (CAC) score. Methods: This cross-sectional analysis of pooled data from 3 large cohorts compared the associations between the 3 CKD-EPI eGFR equations (Cr, CysC, and Cr-CysC) with CIMT and CAC score using multivariable regression analysis. eGFR and CIMT were analyzed as continuous variables. CAC scores were analyzed as a binary variable (detectable calcification versus nondetectable) and as a log10 Agatston score in those with detectable CAC. Results: Thousand four hundred eighty-seven participants were included, and of these 910 (562 HIV+ and 348 HIV−) had CIMT measurements and 366 (296 HIV+ and 70 HIV−) had CAC measurements available. In HIV− participants, GFR estimated by any CKD-EPI equation did not significantly correlate with CIMT or CAC scores. When PLWH were analyzed separately including HIV-specific factors, only GFR estimated using Cr-Cys C correlated with CIMT [β= −0.90, 95% CI: (−1.67 to −0.13) μm; P = 0.023]. Similarly, eGFR correlated with Agatston scores only when using cystatin C-based eGFR [β= −8.63, 95% CI: (−16.49 to −0.77) HU; P = 0.034]. Associations between other eGFR formulas and CAC did not reach statistical significance. Conclusions: In PLWH, preclinical atherosclerosis may be more closely correlated with eGFR using formulae that incorporate CysC measurements than Cr alone. Abstract : Supplemental Digital Content is Available in the Text.